2004
DOI: 10.3146/pnut.31.1.0008
|View full text |Cite
|
Sign up to set email alerts
|

Sicklepod Control in Peanut Seeded in Single and Twin Row Planting Patterns

Abstract: Sicklepod [Senna obtusifolia (L.) Irwin & Barneby] control and peanut pod yield with preemergence applications of dimethenamid and dimethenamid plus diclosulam alone or followed by postemergence application of imazapic were compared when peanut was seeded in single and twin row planting patterns. Sicklepod control was 9% higher when peanut was seeded in the twin row planting pattern (rows spaced 18 em apart on 9l-cm centers) compared with peanut planted in the single row planting pattern (single rows on 9l-cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These results suggest that in a lowinput weed management system for peanut, more rapid canopy closure from the narrow twin row planting pattern does not effectively compensate for the restricted cultivation. Lanier et al (2004b) concluded that twin row planting can improve weed control compared with single row planting but did not eliminate the need for herbicides to protect pod yield a Single rows were spaced 91 cm apart, standard twin rows were spaced 20 cm apart on 91-cm centers, and the narrow twin-row pattern included twin rows spaced 20 cm apart on 46-cm centers.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that in a lowinput weed management system for peanut, more rapid canopy closure from the narrow twin row planting pattern does not effectively compensate for the restricted cultivation. Lanier et al (2004b) concluded that twin row planting can improve weed control compared with single row planting but did not eliminate the need for herbicides to protect pod yield a Single rows were spaced 91 cm apart, standard twin rows were spaced 20 cm apart on 91-cm centers, and the narrow twin-row pattern included twin rows spaced 20 cm apart on 46-cm centers.…”
Section: Resultsmentioning
confidence: 99%
“…The twin-row planting pattern has also been reported to provide greater late-season control of C. esculentus (Grichar et al 1994), D. tortuosum (Brecke and Stephenson 2006; Colvin et al 1985), E. prostrata (Place et al 2010), Ipomoea spp. (Place et al 2010), S. obtusifolia (Brecke and Stephenson 2006; Colvin et al 1985; Lanier et al 2004), U. texana (Colvin et al 1985), tumbleweed ( Salsola tragus L.), and X. strumarium (Brecke and Stephenson 2006) compared with the single-row planting pattern in peanut. However, not all cultivars benefit equally from the twin-row planting pattern.…”
Section: Weed Managementmentioning
confidence: 99%
“…A review of the literature documenting studies focused on evaluation of row spacing and row configuration was conducted as a summary of the work conducted in this area over the last three centuries. Figures 1 and 2 show average yields and relative weed abundance reported across the studies found in the literature review (Hauser and Buchanan 1981;Besler 2004;Brecke and Stephenson 2006;Cardina et al, 1987;Colvin et al, 1985a;Colvin et al, 1985b;Culbreath et al, 2008;Lanier et al, 2004a;Lanier et al, 2004b, Place et al, 2010Sconyers et al, 2007;Wehtje et al, 1984;Yoder, 2003), (Scott Monfort, unpublished data, 2012. Blackville, SC: Clemson University, Edisto Research & Education Center).…”
Section: Introductionmentioning
confidence: 99%